18-month outcomes of heterologous bilateral hand transplantation in a child: a case report. (September 2017) - Amaral, Sandra; Kessler, Sudha Kilaru; Levy, Todd J; Gaetz, William; McAndrew, Christine; Chang, Benjamin; Lopez, Sonya; Braham, Emily; Humpl, Deborah; Hsia, Michelle; Ferry, Kelly A; Xu, Xiaowei; et al.
Summary: Background: Although heterologous vascular composite allotransplantation has become a burgeoning treatment option for adult amputees, there have been no successful cases previously reported in children. Here, we describe the surgical, immunological, and neurorehabilitation details with functional outcomes 18 months after heterologous bilateral hand and forearm transplantation in an 8-year-old child with quadrimembral amputations and a previous kidney transplant. Methods: 2 years of extensive preparation by medical and surgical teams preceded the hand–forearm transplantation of this child. The initial immunosuppressive protocol included thymoglobulin, tacrolimus, prednisone, and mycophenolate mofetil. In July, 2015, our vascularised composite allotransplantation team did the first bilateral hand and forearm transplantation in a child, an 8-year-old boy with previous living-related kidney transplantation. The surgery included four teams working simultaneously on the donor and recipient limbs, aided by customised cutting guides that aimed to reduce ischaemia time. Following an extended length of time in hospital, skin biopsies and close monitoring of renal function and drug concentrations occurred weekly for the first 3 months and were slowly tapered to monthly, and then quarterly. Skin biopsies were also done when tissue rejection was suspected. Paediatric-specific rehabilitation techniques were applied to promote patient engagement during rehabilitation. Progress was assessed by monthly sensory and motor function tests during routine clinic visits and with serial functional brain imaging studies, including structural brain MRI, magnetoencephalography and transcranial magnetic stimulation. Findings: The surgery lasted 10 h and 40 min. Vascular revision of the ulnar artery was required a few hours postoperatively. There were no further immediate postsurgical complications. Rejection episodes occurred throughout the first year but were reversed. An increase in serum creatinine led to the addition of sirolimus at 3 months after transplantation with concomitant reduction in tacrolimus targets. Sensibility to light touch was present by 6 months after transplantation. Intrinsic hand muscle innervation was present by 7–10 months after transplantation. At 18 months, the child had exceeded his previous adapted abilities. As of 18 months after transplantation surgery he is able to write and feed, toilet, and dress himself more independently and efficiently than he could do before transplantation. He remains on four immunosuppressive medications and functional neuroimaging studies have shown motor and somatosensory cortical reorganisation. Interpretation: Hand transplantation in a child can be surgically, medically, and functionally successful under carefully considered circumstances. Long-term data on the functional trajectory, neurological recovery, psychological sequelae, and the potential late effect of immunosuppression are still needed to support broader implementation of paediatric vascular composite allotransplantation. Funding: The Children's Hospital of Philadelphia.